The Effects of Different Methods of Self-Talk (Motivational, Instructional, and Combined) on Physical Efficacy, Acquisition and Learning of Dart Throw Task - Ahmadreza Movahedi; Abbas Bahram; Sahar Bordbar (رشد و یادگیری حرکتی ورزشی, 2016)
The aim of the present study was to investigate the effect of different methods of self-talk (motivational, instructional, and combined) on acquisition and learning of a motor perceptional task (dart) and physical efficacy in female students aged between 13 and 18. 48 female students (mean age 15.46 yr) who were novice at dart throwing voluntarily participated in this study. Participants were divided into 4 groups including motivational self-talk, instructional self-talk, motivational-instructional self-talk and physical practice (12 students in each group) following an initial instructional session and pretest. The intervention included 10 sessions of acquisition, 2 sessions of retention test and one session of transfer test. One-way ANOVA and ANOVA with repeated measures were used to analyze data. Results showed that combined (motivational-instructional) and the instructional self-talk groups improved dart throwing performance in acquisition, immediate and delayed retention sessions in 13-18-year-old students compared with the motivational self-talk and physical exercise groups. Instructional self-talk group showed the best performance in transfer test while the other three groups showed almost similar performances. The results also showed that different interventions had no significant effects on physical self-efficacy of the participants.